2008
DOI: 10.2478/v10009-008-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Lead and cadmium content in the meat tissues of fish from water ecosystems in the vicinity of a pesticide tomb

Abstract: Lead and cadmium levels were determined in the meat tissues of roach, bream, and carp netted in a lake and in fish ponds threatened by a pesticide tomb and in control basins in northeastern Poland. Concentrations in roach ranged from 20 to 124 μg kg -1 of Pb and from 1 to 19 μg kg -1 of Cd. In bream they were from 4 to 280 μg kg -1 of Pb and 2 to 28 μg kg -1 of Cd, while in carp they were from 9 to 82 μg kg -1 of Pb and 2 to 260 μg kg -1 of Cd. The metal concentrations were low; no result exceeded admissible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…After mineralization at 450 • C, the residue was etched with a mixture of concentrated nitric acid (HNO 3 ,) and perchloric acid (HClO 4 , 70%) (Wieczorek et al, 2005). The metal levels were determined using a flame atomic absorption spectrophotometer PYE UNICAM 939/959 model after extraction into the organic phase with 4-methylpentan-2-one (Skibniewska et al, 2008). The components were analyzed at the Central Analytical Laboratory, University of Warmia and Mazury in Olsztyn.…”
Section: Chemical Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…After mineralization at 450 • C, the residue was etched with a mixture of concentrated nitric acid (HNO 3 ,) and perchloric acid (HClO 4 , 70%) (Wieczorek et al, 2005). The metal levels were determined using a flame atomic absorption spectrophotometer PYE UNICAM 939/959 model after extraction into the organic phase with 4-methylpentan-2-one (Skibniewska et al, 2008). The components were analyzed at the Central Analytical Laboratory, University of Warmia and Mazury in Olsztyn.…”
Section: Chemical Quantificationmentioning
confidence: 99%
“…Studies by Grzybowski et al (2004Grzybowski et al ( , 2005 and Skibniewska et al (2004) addressed the effect of pesticide tombs located in the region of Warmia and Mazury on flora and fauna as well as on the bioaccumulation of organochlorine pesticides and heavy metals in aquatic ecosystems (Skibniewska et al, 2008). The results of these studies demonstrated that despite the presence of low levels of contaminants including persistent organic pollutants (POP) and heavy metals in most of the environmental samples from the region of Warmia and Mazury, there is still a risk that areas adjacent to the pesticide tombs may contain increased concentrations of contaminants.…”
mentioning
confidence: 98%
“…However, there is a risk associated with the consumption of fish, as pollutants from the environment may enter the body (Jia et al 2017). Water and soil contamination lead to the transfer of heavy metals (e.g., mercury, arsenic, lead) and chemical compounds into living organisms, where they accumulate in fish tissues and organs (Skibniewska et al 2008).…”
Section: Influence Of Pond Water Management On Trace Element Content ...mentioning
confidence: 99%
“…Recently, various dumps have become sources of serious environmental contamination. Very often they were built without due care which allowed leaks to occur from the deposits (Skibniewska et al, 2008). Every kind of waste, including pesticides, contains some quantity of heavy metals that can escape into the soil and ground water.…”
mentioning
confidence: 99%